2014
DOI: 10.1016/j.enpol.2013.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Predicting oil price movements: A dynamic Artificial Neural Network approach

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…A combination of the Elman and Jordan was used for prediction of health condition of gears [21]. The oil price movement was forecasted with nonlinear autoregressive model with exogenous input (NARX) network [22]. A MLP with output feedback was used for urban storm water run-off prediction [23].…”
Section: Previous Work Donementioning
confidence: 99%
See 1 more Smart Citation
“…A combination of the Elman and Jordan was used for prediction of health condition of gears [21]. The oil price movement was forecasted with nonlinear autoregressive model with exogenous input (NARX) network [22]. A MLP with output feedback was used for urban storm water run-off prediction [23].…”
Section: Previous Work Donementioning
confidence: 99%
“…Forecasting from historic values[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. 2 Prediction of a complete time series in a specific time interval from another distinct time series[27].3 Prediction of complete time series in a specific time interval from multiple and distinct time series (proposed solution) Neural Comput & Applic…”
mentioning
confidence: 99%
“…Previous researchs showed that the main factors causing the world price of gold shortterm T (USD / troy ounce) fluctuations are: the dollar index x1, Dow-Jones index x2, crude oil prices x3 ($ / bbl), United States 30-year bond x4, euro against the dollar (one euro equivalent to USD) x5, etc [6][7][8]. In this paper, the world gold price April 1, 2013 to November 10, 2013 of 188 short-term factors and the main daily data (except holidays) as 188 samples of short-term price fluctuations on the world gold empirical analysis.…”
Section: The Experimental Data and The Environmentmentioning
confidence: 99%
“…So τ , m is often used to solve ideological unity [5]. Advantage of the current gold price prediction algorithm is that they mainly use neural network algorithm, support vector machines and other algorithms [6][7], because the least squares support vector machine (LSSVM) has ability of high training speed, good generalization.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical work utilizing the power of these models is on the rise, but with mixed results. For example, Godarzi et al [6] found that the proposed dynamic Artificial Neural Network model achieves the improved forecasting accuracy than the time series and static neural network model [6]. Yu et al [7] found that Artificial Neural Network (ANN) outperforms Autoregressive Moving Average (ARMA) model, but has room for further improvement using ensemble algorithms.…”
Section: Introductionmentioning
confidence: 99%